161 Optogenetic Stimulation of Cerebellar Dentate Nucleus Promotes Persistent Functional Recovery After Stroke. (August 2015) - Ishizaka, Shunsuke; Cheng, Michelle; Shah, Aatman M.; Wang, Eric; Bautista, Alex R.; Sun, GuoHua; Steinberg, Gary K.
Abstract : INTRODUCTION: Poststroke brain stimulations are promising neurorestorative techniques because they allow direct manipulation of the target area's excitability. Previously, we demonstrated that optogenetic neuronal stimulation of the ipsilesional primary motor cortex promotes functional recovery. To determine an optimal brain stimulation target, we tested whether optogenetic neuronal stimulation of the contralesional cerebellar dentate nucleus (cDN) can promote recovery. We hypothesized that stimulation of cDN may be more effective, because it sends excitatory outputs to multiple cerebral regions. METHODS: Thy-1-ChR2-YFP line-18 transgenic mice underwent stereotaxic fiber cannula implant in cDN, followed by transient middle cerebral artery occlusion. Control nonstimulated mice, short-term stimulated mice (day 5-14) and long-term stimulated mice (day 5-28) were used. Sensorimotor behavior tests were used to assess their recovery at day 0, 4, 7, 10, 14, 21, and 28 poststroke. Mice were euthanized at various time points for immunohistochemistry and Western blots. RESULTS: Our data showed that stimulated stroke mice recovered with significant improvement in distance traveled ( P < .01) and faster speed on the rotating beam at day 14 poststroke ( P < .05). The short-term simulation group continued to recover after day 14 without further stimulations and the long-term stimulation group did not show additional enhanced recovery, indicating that the functional outcome of cDN stimulation is persistent. Western blotting showed that stimulated stroke mice exhibited a significant decrease in pCREB and total CREB expression in ipsilesional M1 ( P < .01) and an increase in GAP43 expression in ipsilesional S1 ( P < .05). CONCLUSION: Our data suggest that cDN stimulations poststroke can promote functional recovery and this prorecovery effect is persistent. Recovery of cDN-stimulated stroke mice is associated with upregulation of plasticity marker GAP43 and downregulation of CREB signaling. Current studies examine the effects of cDN stimulations on axonal sprouting and the contribution of CREB in recovery. cDN could be a promising brain stimulation target for stroke recovery.